THE TEACHER’S AND STUDENTS’ PERCEPTION ON PROJECT BASED LEARNING IN NURSING DEPARTMENT - Abdul Halim; Dewi Wardah Mazidatur Rohmah (English Education Department, 2020)
The study was aimed at investigating the students’ and teacher’s perceptions in utilizing technology-based classroom instruction in learning English for specific purpose (ESP) as an effort of enhancing the quality of students’ participation. In education, active participation of all stakeholders such as students, teachers, and policy makers is important so that the education goals can be achieved. The development of industrial revolution 4.0 disrupts every aspect of life including education. Teacher should take advantage of the current technology development for enhancing the quality of teaching process. The study employed survey study research method. One teacher and 72 students from nursing department were involved in the study and an electronic questionnaire with close-ended and open-ended questions was used to collect the data. The data was analyzed with the stages of data collection, data reduction, data display and conclusion drawing. The findings of the study showed that both the teacher and the students have perceived positively towards the project based learning in their ESP class. In addition, this type of learning process enhances students’ active participation